Enhancing Physics Understanding through Project-Based Learning and Discovery Learning: A Classroom Implementation Study in a Resource-Limited Indonesian High School - Basriyah, Khusnul; Melisa (The Indonesian Institute of Science and Technology Research, 2025)
This study examines the implementation of Project-Based Learning (PjBL) and Discovery Learning models to enhance students’ understanding of physics concepts at SMAN 1 Rangsang Barat, located in Kepulauan Meranti Regency, Riau Province, Indonesia. Operating under the Merdeka Curriculum, which emphasizes student-centered learning, competency development, and character formation, the school faces a significant challenge: the absence of a physics laboratory and limited access to experiment kits. To overcome these constraints, the teacher designed low-cost, student-built experimental tools, including marble roller coaster models for kinetic and potential energy, renewable and non-renewable energy process mock-ups, measurement activities, and simple paper-circuit traffic lights for dynamic electricity lessons. A qualitative classroom action research design was used, involving observation, documentation, and assessment of learning outcomes. Results show improved student motivation, enhanced science process skills, and significant increases in physics learning outcomes, with most students achieving scores above the minimum competency criteria. The study concludes that PjBL and Discovery Learning are effective and adaptable even in low-resource environments. Recommendations for broader implementation and sustainable innovation are provided.